A Comprehensive Protocol for Bayesian Phylogenetic Analysis Using MrBayes: From Sequence Alignment to Model Selection and Phylogenetic Inference - Jinxing Wang; Fangmin Chen; Xu Xiao; Xinyao Yang; Wanting Xia (Bio-Protocol)
Bayesian phylogenetic analysis is essential for elucidating evolutionary relationships among organisms. Traditional methods often rely on fixed models and manual parameter settings, which can limit accuracy and efficiency. This protocol presents an integrated workflow that leverages GUIDANCE2 for rigorous sequence alignment, ProtTest and MrModeltest for robust model selection, and MrBayes for phylogenetic tree estimation through Bayesian inference. By automating key steps and providing detailed command-line instructions, this protocol enhances the reliability and reproducibility of phylogenetic studies.